2008
DOI: 10.1097/01.ccm.0000297885.60037.6e
|View full text |Cite
|
Sign up to set email alerts
|

Effect of obesity on intensive care morbidity and mortality: A meta-analysis*

Abstract: Obesity in critically ill patients is not associated with excess mortality but is significantly related to prolonged duration of mechanical ventilation and intensive care unit length of stay. Future studies should target this population for intervention studies to reduce their greater resource utilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
275
5
24

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 440 publications
(324 citation statements)
references
References 49 publications
20
275
5
24
Order By: Relevance
“…Overall, 30% of ICU patients are obese and 7% morbidly obese (2). Obesity seems to confer a higher risk for development of common conditions in critically ill patients such as the acute respiratory distress syndrome (ARDS) (3) (4).…”
Section: Introductionmentioning
confidence: 99%
“…Overall, 30% of ICU patients are obese and 7% morbidly obese (2). Obesity seems to confer a higher risk for development of common conditions in critically ill patients such as the acute respiratory distress syndrome (ARDS) (3) (4).…”
Section: Introductionmentioning
confidence: 99%
“…The impact of BMIs in the requirement for MV and the outcome for those patients are mixed with most of the reports addressing the obese population [11,19,[45][46][47][48][49]. Pulmonary physiological changes related to elevated BMI includes a decreased lung compliance with a lower total lung capacity, functional residual capacity and residual volume and an increased airway resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Population based studies suggest a U or J shaped curve indicating a higher mortality at the extremes of BMIs [8][9][10]. The association of BMI with mortality in the intensive care unit (ICU) is controversial with reports suggesting no relation [11][12][13], increased [14][15][16] or decreased hospital mortality [17]. The role of BMI for length of stay (LOS) on mechanical ventilation (MV) and ICU LOS is equally inconsistent [11,[18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…They found no associated mortality risk with a BMI of Ն 40 kg/m 2 . Akinnusi et al 6 published another meta-analysis that compared the mortality of subjects with a BMI of Ͼ 30 kg/m 2 with that of subjects with a BMI of Ͻ 30 kg/m 2 . The authors found no difference in ICU mortality, but did find an improvement in mortality at the time of discharge.…”
mentioning
confidence: 99%
“…Data from the medical literature is inconsistent. Multiple meta-analyses suggest a lower mortality rate among critically ill obese subjects, [5][6][7] known as the obesity paradox. Oliveros and Villamor 5 showed a lower risk of mortality among medical and surgical ICU subjects with a body mass index (BMI) between 18.5 and 24.9 kg/m 2 compared with those with a BMI between 30 and 39.9 kg/m 2 .…”
mentioning
confidence: 99%